Assessing The Information-Seeking Behavior of Cianjur Earthquake Survivors: A Study of Information Needs and Access - Ruli Triani; Riyan Adi Putra (Librarianship in Muslim Societies, 2024)
In the midst of a disaster such as an earthquake, one of the most important things is the dissemination of the right information. Searching for the right information can affect the safety of one's life. Therefore, studies related to information seeking behavior during disasters can illustrate how a person searches for information in response to circumstances during a disaster. This study aims to determine how much the level of conformity of information seeking behavior carried out by victims of the Cianjur earthquake disaster with the disaster information seeking behavior model. This research uses quantitative methods with a case study approach in the Cianjur area. The population in this study were earthquake victims in Cianjur with productive age (15-57 years). The sample used was 100 respondents using accidental sampling technique. The hypothesis in this study is the level of information seeking behavior of earthquake victims in Cianjur in accordance with the disaster information seeking behavior model. The results of the study obtained a score on the first warning dimension of 2.39. The dimension of recipient characteristics amounted to 2.83 and message characteristics amounted to 3.59. The information source horizon dimension was 3.03 and the feedback dimension was 3.36. Based on these results, an average score of 3.04 was obtained. The score is in the interval 2.51 - 3.25, which indicates that the information seeking behavior of earthquake victims in Cianjur is at the "appropriate" level with the disaster information seeking behavior model.